Pengaruh Pendidikan Kesehatan Metode Demonstrasi Tentang SADARI Terhadap Kemampuan Melakukan SADARI Pada Remaja Putri SMA Diponegoro Dampit - Puput Indrya Lestari; Herawati Mansyur; Wandi . (Jurnal Pendidikan Kesehatan, 2020)
The death rate of cancer in Indonesia is still high. One of the causes is breast cancer. Efforts to prevent delays in handling can be by way of providing health education about breast self examination. Breast self examination is early detection efforts to determine abnormalities in the breast. This study aims to determine the influence of health education methods of demonstration about breast self examination of the ability to realize in young women in senior high school Diponegoro Dampit. This research method uses pre experimental design with One Group Pretest Posttest. The population of teenage girls are eleven and twelve class degrees of IPA which amounted to 26 people, using Proportional Stratified Random Sampling technique and got sample number of 24 respondents who comply the inclusion criteria. Instrument of this research use checklist. The test used is Wilcoxon Signed Rank Test with T approximately same as 0,05 using a computer. The result showed that p value 0.000 is smaller than T approximately 0,05, then Ho was rejected which means there is Influence Of Health Education Methods Of Demonstration About Breast Self Examination Of The Ability To Realize In Young Women Senior High School Diponegoro Dampit. There are factors that influence the result of the research namely age, where all respondents are 17 until 20 years old. This age group includes late adolesence, where someone has started toward maturity and a personal way of thinking will also become more mature. Based on this research it is hoped that this health education can be used as a knowledge for early prevention of breast cancer.